Meningkatkan Hasil Belajar Bahasa Indonesia “Menulis Puisi Bebas” Melalui Metode Real Experience Pada Siswa Kelas VI MI DDI Ujung Lero - Maipah (Publikasi Indonesia, 2022)
This study aims to determine whether the application of the Real Experience learning method can improve the learning outcomes of Indonesian Language on the subject of writing free poetry for class VI MI DDI Ujung Lero for the 2021/2022 academic year consisting of 22 students, namely 13 boys and 9 girls. This research is a Classroom Action Research (PTK) consisting of 2 cycles, each cycle of which is a series of activities consisting of 4 stages, namely planning, implementation, observation / observation and, reflection. This classroom action research (PTK) uses data collection, namely written tests, observation sheets and documentation. Data analysis was carried out by comparing the achievement of learning outcomes for each cycle with a marked increase in classical completeness criteria. Based on the results of this study, it shows that the application of learning methods can improve student learning outcomes. This can be proven from the pre-cycle results before applying the Real Experience method there were 54.54% (12 students) who met the KKM, while 45.45% (10 students) had not met the KKM increased in cycle I which showed that students reached the 68.18% (15 students) Classical completeness criteria while those who had not met the KKM 31.81% (7 students) with an average score of 77.9. In cycle II, the Classical Completeness Criteria was 86.36% (19 students) while those who had not met the KKM were 13.63% (3 students) with an average of 84.5. Thus, the learning outcomes obtained by students from cycle I to cycle II increased by 18.18%.